Step-by-step explanation:Radical Equation entered : √2x-3 = 6Step by step solution :STEP 1:Isolate the square root on the left hand side Radical already isolated √2x-3 = 6STEP 2:Eliminate the radical on the left hand side Raise both sides to the second power (√2x-3)2 = (6)2 After squaring 2x-3 = 36STEP 3:Solve the linear equation Rearranged equation 2x -39 = 0 Add 39 to both sides 2x = 39 Divide both sides by 2 A possible solution is : x = (39/2)STEP 4:Check that the solution is correct Original equation √2x-3 = 6 Plug in (39/2) for x √2•(39/2)-3 = 6 Simplify √36 = 6 Solution checks !! Solution is: x = (39/2)